(untitled) (Indian Journal of Animal Production and Management, 2016)
The present study was carried out to evaluate the toxic effect of lead and protective efficacy of Withania somnifera root powder on the growth and performance of chickens for a period of 60 days. The general performance of birds was evaluated on the basis of clinical signs, average weekly body weight, feed consumption, body weight gain and feed conversion ratio (FCR). In control group (group I), birds were active and healthy and did not show any untoward clinical sign. While in 250 ppm (group II) and 400 ppm (group III) lead treated birds showed signs like dullness, depression, weakness, letharginess with loss of appetite. Loose droppings were seen in group III. Clinical signs were less severe with less number of birds affected in 250 ppm lead+WSRP (group IV) and 400 ppm+WSRP (group V) birds as compared to groups II and III. No mortality was seen in any of the group. A significant dose and time dependent decrease in body weight, feed consumption, body weight gain and significant increase in FCR were observed in groups II and III as compared to group I. However, in groups IV and V, a significant lesser decrease in body weight, feed consumption, body weight gain and significantly less increase in FCR observed as compared to groups II and III observed, respectively. The present investigation indicated the adverse effects of lead acetate on performance of broilers at 250 and 400 ppm and Withania somnifera root powder offering protection against lead toxicity in chickens.